In Vivo Bioluminescence Imaging in a Rabbit Model of Orthopaedic Implant-Associated Infection to Monitor Efficacy of an Antibiotic-Releasing Coating. (20th February 2019) - Miller, Robert J.; Thompson, John M.; Zheng, Jesse; Marchitto, Mark C.; Archer, Nathan K.; Pinsker, Bret L.; Ortines, Roger V.; Jiang, Xuesong; Martin, Russell A.; Brown, Isabelle D.; Wang, Yu; Sterling, Robert S.; et al.
Abstract : Background: In vivo bioluminescence imaging (BLI) provides noninvasive monitoring of bacterial burden in animal models of orthopaedic implant-associated infection (OIAI). However, technical limitations have limited its use to mouse and rat models of OIAI. The goal of this study was to develop a larger, rabbit model of OIAI using in vivo BLI to evaluate the efficacy of an antibiotic-releasing implant coating. Methods: A nanofiber coating loaded with or without linezolid-rifampin was electrospun onto a surgical-grade locking peg. To model OIAI in rabbits, a medial parapatellar arthrotomy was performed to ream the femoral canal, and a bright bioluminescent methicillin-resistant Staphylococcus aureus (MRSA) strain was inoculated into the canal, followed by retrograde insertion of the coated implant flush with the articular surface. In vivo BLI signals were confirmed by ex vivo colony-forming units (CFUs) from tissue, bone, and implant specimens. Results: In this rabbit model of OIAI (n = 6 rabbits per group), implants coated without antibiotics were associated with significantly increased knee width and in vivo BLI signals compared with implants coated with linezolid-rifampin (p < 0.001 and p < 0.05, respectively). On day 7, the implants without antibiotics were associated with significantly increased CFUs from tissue (mean [and standard error of the mean], 1.4 × 10 8 ± 2.1 × 10 7 CFUs; p < 0.001), bone (6.9 × 10 6 ± 3.1 × 10 6 CFUs; p < 0.05), and implant (5.1 × 10 5 ± 2.2 × 10 5 CFUs; p < 0.05) specimens compared with implants with linezolid-rifampin, which demonstrated no detectable CFUs from any source. Conclusions: By combining a bright bioluminescent MRSA strain with modified techniques, in vivo BLI in a rabbit model of OIAI demonstrated the efficacy of an antibiotic-releasing coating. Clinical Relevance: The new capability of in vivo BLI for noninvasive monitoring of bacterial burden in larger-animal models of OIAI may have important preclinical relevance.